S-Heptazine N-ligand based luminescent coordination materials: synthesis, structural and luminescent studies of lanthanide–cyamelurate networks. Issue 39 (16th September 2022) - Essalhi, Mohamed; Mohan, Midhun; Marineau-Plante, Gabriel; Schlachter, Adrien; Maris, Thierry; Harvey, Pierre D.; Duong, Adam
Abstract : Coordination modes and hydrogen bonding networks of the lanthanide cyamelurate series and its luminescence study. Abstract : Various series of lanthanide metal–organic networks denoted Ln–Cy (Ln = La, Ce, Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb), were synthesized under solvothermal conditions using potassium cyamelurate (K3 Cy ) and lanthanide nitrate salts. All obtained materials were fully characterized, and their crystal structures were solved by single-crystal X-ray diffraction. Four types of coordination modes were elucidated for the Ln–Cy series with different Ln 3+ coordination geometries. Structural studies were performed to compare the various coordination compounds of the Ln–Cy series. Moreover, the cyamelurate linkers of rich π-conjugated and uncoordinated Lewis basic sites were used as an absorbing chromophore to enhance the luminescence quantum efficiency, the band emission and the luminescence lifetime of the coordinated Ln metal centers. Solid-state UV-visible measurements combined with density functional theory (DFT) and time-dependent density functional theory (TDDFT) calculations were performed to further explore luminescent features of the Ln–Cy series and their origins.